Numerical Minimum Competence Assessment for Increasing Students’ Interest in Mathematics - Hanna Wijaya; Rina Maryanti; Verra Wulandary; Asep Rudi Irawan (ASEAN Journal of Science and Engineering Education, 2022)
The aim of this research is whether the numerical minimum competency assessment can be one of the learning media to increases students' interest, especially in mathematics. To support this research, we used quantitative research methods, namely data collection was carried out using a series of research instruments in the form of a numerical minimum competency assessment test, both pre-test and post-test using google form media. This numerical minimum competency assessment test was given to find out how far the ability and interest of students in mathematics. There were 10 questions given to 11 students. Based on the results of the study, the number of students' interest in learning scores increased from 500 to 900. This happened because the minimum competency assessment media literacy got a positive response from students. After all, the minimum competency assessment questions used pictures and stories so that it could be said that the minimum competency assessment was interesting for students. Therefore, it could be concluded that the use of minimum competency assessment media literacy in learning mathematics increased students' interest in learning.